Explaining the mixed outcomes from hosting major sporting events in promoting tourism (2019)
We report on a study of the longitudinal effects of the 2014 World Cup on the host Brazil's overall image and for tourism intentions in three other countries (total sample = 207). Brazil's image declined significantly 2013–2014 on some but not all measures and improved amongst a significant minority. The mixed outcomes are explained by the moderating effects of respondent personality, their involvement in the event (rather than in the sport being hosted) and their perception of the news they had been exposed to. Those who held a relatively negative attitude towards Brazil before the event tended to be positively influenced by positive media, watching the closing ceremony and by searching for news about Brazil. Those relatively high in Openness to Experience were less likely to report a reduction in attitude. The net effect was an improvement in tourism intentions, mainly among those less likely to visit pre-event and a decline among most others. © 2019 Elsevier Ltd